2019
DOI: 10.1039/c9cc02030f
|View full text |Cite
|
Sign up to set email alerts
|

Copper-catalyzed ring-opening C(sp3)–N coupling of cycloketone oxime esters: access to 1°, 2° and 3° alkyl amines

Abstract: Access to 1°, 2° and 3° alkyl amines through copper-catalyzed C(sp3)–N coupling of cycloketone oxime esters was realized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…The desired cyano‐containing alkyl amines were synthesized in good to excellent yields and have proven to be versatile synthetic building blocks for multifarious organic compounds (See Figure 97). [103] …”
Section: Miscellaneous Cyanation Techniquesmentioning
confidence: 99%
“…The desired cyano‐containing alkyl amines were synthesized in good to excellent yields and have proven to be versatile synthetic building blocks for multifarious organic compounds (See Figure 97). [103] …”
Section: Miscellaneous Cyanation Techniquesmentioning
confidence: 99%
“…Based on the above observations and previous reports 6066,68,69 , the proposed mechanisms of two catalytic processes were depicted in Fig. 6.…”
Section: Resultsmentioning
confidence: 59%
“…For example, Liu reported the copper-catalyzed C-N bond formation of free anilines and cyclobutanone oxime esters with 6,6′-dimethyl-2,2′-bipyridine 162 as the ligand, 61 while Fu and co-workers found that a Cu(OTf) 2 /1,10-phen catalytic system was more effective for secondary amines. 62 In a report by Shi, the use of fac-Ir(ppy) 3 under visible light irradiation can promote the reaction of secondary amines. 63 Depending on the nature of the amines, Guo systemically investigated the copper-catalyzed ring-opening amination of cycloketone oxime esters using different ligands with or without visible light irradiation.…”
Section: C-n Bond Formationmentioning
confidence: 99%